2008 First International Conference on Intelligent Networks and Intelligent Systems 2008
DOI: 10.1109/icinis.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Analysis of a Dynamic Discrete PSO Algorithm

Abstract: The particle swarm optimization(PSO) algorithm has exhibited good performance on continuous optimization problems in static environment. However, there are lots of real-world optimization problems that are dynamic and discrete, which is a new research field of PSO. So a dynamic discrete PSO(DDPSO) algorithm is proposed in this paper. In this algorithm, we design a new strategy of environmental monitoring and response. When environment is changed, it can be apperceived by the change of fitness and position of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The better performance of PSO is due to the continuity of the problem of WSN deployment. Based on the research [ 91 , 92 ], the PSO algorithm is suitable for continuous optimization problems. WSN deployment is a continuous problem as the sensor nodes can be located at any position in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The better performance of PSO is due to the continuity of the problem of WSN deployment. Based on the research [ 91 , 92 ], the PSO algorithm is suitable for continuous optimization problems. WSN deployment is a continuous problem as the sensor nodes can be located at any position in the region.…”
Section: Discussionmentioning
confidence: 99%
“…To generate a new particle p i k+1 , the final swap sequence is applied on particle p i k mentioned in above equation (1). From [14], it can be found that the convergence condition for this PSO is given by,…”
Section: Discrete Particle Swarm Optimizationmentioning
confidence: 99%